Translating, Contexting, and Institutionalising Knowledge Translation Practices in Northern Australia: Some Reflections; Comment on "Sustaining Knowledge Translation Practices: A Critical Interpretive Synthesis" - Alexandra Edelman; Stephanie M. Topp (Kerman University of Medical Sciences, 2023)
In this commentary, we reflect on how the three processes of translating, contexting, and institutionalising knowledge translation (KT) practices, as introduced in a critical interpretive synthesis on sustaining KT, might be drawn on to improve KT sustainability in the northern Australian health system, and some likely challenges. The synthesis provides a useful reminder that health systems are social systems and offers an analytical framework against which to map approaches that aim to align knowledge production and utilisation. By positioning "places" of knowledge utilisation and actor roles and networks as key to KT sustainability, the framework also offers the potential to draw attention to non-clinical settings, actors, and relationships that are central to improving health, but that may be historically neglected in KT research and scholarship.